Menakar Risiko Pembiayaan Bank Syariah di Era Digital - Asrofi, Ahmad Khoirudin; Sanawati, Ciptia Khoirulina; Sya’idun, Sya’idun (Lembaga Penelitian dan Pengembangan Masyarakat IAINU Kebumen, 2024)
Sharia banking business activities in Indonesia will always be faced with risks related to its function as a financial intermediation institution. The development of the internal and external environment of sharia banking is increasingly complex. Currently, Islamic banks are facing new challenges that have the potential to affect stability and security in the digital era. The aim of this research is to identify and analyze various risks faced by Islamic banks in the context of digital era financing. The type of research used is library research, namely research carried out by collecting data and theoretical basis by studying books, scientific works, articles, related journals and other trusted sources that are relevant to the topic. These findings show that the application of digital technology to sharia banking services provides many benefits in the form of ease of access for customers. Apart from that, the digital era also creates new risks such as cyber security threats, technological failures, and non-compliance with regulations which can disrupt the stability of banking liquidity.